The positive interfaith relationships in the culture of peace seminar a rhetorical analysis - Gopo, Althea Astrid T.
In a communication situation, culture may serve as both a uniting and a dividing factor between he individuals involved. Communicators who do not agree in these terms are unlikely to have a harmonious relationship, or effectively perform in a group together. The Culture of Peace Seminar, however, which was adopted by the Davao Ministerial Interfaith, Inc., (DMI), has aided an organization in transcending the challenge of welcoming individuals of diverse religious orientations, establishing positive interfaith relationships. Hence, this sought to understand how the positive interfaith relationships are established among the members within the organization despite differences in religious standpoints by magnifying the rhetoric to which it turned to in the aforementioned seminar. To arrive at a satisfactory and sufficient understanding of the interaction, the study focused on describing the conduct of the seminar and, eventually, provided an analysis of how the organization has delivered its message through such- identifying the strategies that have been employed and baring the motives that lie behind, through the Burkean/Dramatistic Pentad. Moreover, the study was generated a better understanding of the factors that actually lead to how the seminar has affected its participants in the seminar that it did by utilizing the presuppositions put forward by the Symbolic Convergence Theory. The utilization of the two communication theories, which supplemented each other, had provided the study the expediency of presenting an efficient way to understand the communication situation of interest in both ends. Through the accomplishment of this study, the organization of interest would be able to improve or work out strategies that effectively communicates not only their vision as an organization, but would also contribute to achieving the desired ends of the conduct of the seminar. That is, through identifying important points hat greatly influences the conduct and the outcome of the seminar. Furthermore, the study could later on be a significant contribution in facilitating a better understanding of the complexities of religion, facilitating appreciation of these religious groups, going beyond the biased opinions and views that have been formed for them. Thus, it would amount to a small contribution in the advocacy promoting the peace culture in Mindanao
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication